2017
DOI: 10.1186/s13002-017-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plants used by local inhabitants of Jakholi block, Rudraprayag district, western Himalaya, India

Abstract: BackgroundEthnomedicinal knowledge of the Indian Himalayas is very interesting because of the wide range of medicinal plants used in traditional medical practice. However, there is a danger of knowledge being lost because the knowledge sharing is very limited and passed on orally. The present study is the first ethnomedicinal study in Jakholi area of Rudraprayag district of Northwestern India. The aim of present study was to identify traditional medicinal plants used by the inhabitants to treat different ailme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(70 citation statements)
references
References 29 publications
14
54
1
1
Order By: Relevance
“…The most dominant habitus used of medicinal plants in Wonokerto was herbaceous plant (38%), followed by tree (29%), shrub (24%), liana (7%) and grass (2%) ( Figure 3B). This is similar to the results on the medicinal plants found in the Jakholi block, Himalayan India that comprised of 56% of herbaceous plant, 23% of tree and 37% roots (Sing 2017). On the other hand, the most widely used part of the plant was leaf (55%), followed by fruit (19%), tuber (14%), stem (5%), and roots, water, seeds and flowers (each accounted for 1-2%) (Figure 3.A).…”
Section: The Habitus the Part And The Serving Methods Of Medicinal Plsupporting
confidence: 90%
See 2 more Smart Citations
“…The most dominant habitus used of medicinal plants in Wonokerto was herbaceous plant (38%), followed by tree (29%), shrub (24%), liana (7%) and grass (2%) ( Figure 3B). This is similar to the results on the medicinal plants found in the Jakholi block, Himalayan India that comprised of 56% of herbaceous plant, 23% of tree and 37% roots (Sing 2017). On the other hand, the most widely used part of the plant was leaf (55%), followed by fruit (19%), tuber (14%), stem (5%), and roots, water, seeds and flowers (each accounted for 1-2%) (Figure 3.A).…”
Section: The Habitus the Part And The Serving Methods Of Medicinal Plsupporting
confidence: 90%
“…This is because they believe that the leaves have the highest efficacy, easy to obtain, do not damage the trees and easily sprout again, as well as having soft fibers. In addition, the leaves are one of the organs that contain high carbohydrates, minerals, and vitamins, and also easily found (Abbas 2017;Setyowati and Wardah 2007;Sing 2017). However, it is different from the results obtained in Jeju Island, which reporting the roots as the most widely used part for medicinal purposes, followed by fruit, leaves, and seeds (Song et al 2013).…”
Section: The Habitus the Part And The Serving Methods Of Medicinal Plmentioning
confidence: 99%
See 1 more Smart Citation
“…Community knowledge on the use and management of wild plant resources has always been integral to the survival, sustenance, and adaptation of human cultures [46,50,56]. This study revealed 70 medicinal plant species being used by the local marginal community of which 21 are the most extensively used species to treat various ailments.…”
Section: Resultsmentioning
confidence: 97%
“…This can be achieved by capacity building of herbal practitioners and education of new generations which will have substantial impact on the long-standing sustainability of herbal knowledge [45]. Furthermore, there is an urgent need to document this information, as it is rapidly declining due to in uence of pharmaceutical medicines [46]. Thus, it is important to collect this information and develop a data base of medicinal plants for future research and potential development of new herbal medicines.…”
Section: Discussionmentioning
confidence: 99%